Simple capacitive floor occupancy sensor for determining the pattern of a walking person - Arshad, Atika; Khan, Sheroz; Tasnim, Rumana (Institute of Electrical and Electronics Engineers Inc., 2018)
Human motion detection is a crucial factor for security and surveillance applications. Among all available sensors, capacitive sensors have proven to be advantageous for human motion recognition and tracking due to their cost-effectiveness and intrusive abilities. This kind of sensor is also capable of sensing targets from a remote distance, especially for elderly monitoring at home or care centers. The purpose of this paper is to inspect human motion in an indoor atmosphere to monitor the distinctiveness of an individual person in a specific area by deploying a capacitive-based floor detector. Keeping this aim in mind, a model of capacitive sensing technique for detecting human motion in an indoor environment has been developed. The results attained in this paper are of time analysis of capacitance transducer signals which were obtained in a laboratory environment, measuring the performance of the system. As the mobile human goes toward or far from the capacitive sensors, the capacitance of the system will be varied. This is when the occupancy state of the implemented sensors will indicate the movement of human targets.